Pengembangan Sistem Informasi Presensi Siswa Berbasis Website Untuk Monitoring Kehadiran Siswa Menggunakan Framework CodeIgniter - Muhammad, Rizky; Sarmidi, Sarmidi; Muhammad, Taofik (Yayasan Kawanad, 2026)
Manual attendance recording at SMKN 1 Tasikmalaya has produced recurring problems: clerical errors, delayed recapitulation, and limited administrative visibility into student presence patterns. A web-based student attendance information system was developed using the CodeIgniter framework to address these operational shortcomings. The study followed a Research and Development (R&D) approach structured around the ADDIE model, proceeding through five stages — analysis, design, development, implementation, and evaluation. The system was built on PHP and MySQL, supported by standard web technologies. Functional testing was conducted using Black Box Testing, while system feasibility was assessed through the TELOS method covering technical, economic, legal, operational, and schedule dimensions. The TELOS assessment returned a composite score of 93.6, placing the system in the Very Feasible category. Black Box Testing confirmed that all primary functions performed as specified. The resulting system supports structured attendance recording, data management, and recapitulation, and was judged suitable for operational deployment within the school environment.